The way to solve this sort of set of equations is to substitute a value for one of the variables.

If you look at the first equation, you see that you can easily get a value for y. You do that by subtracting 4x from both sides of the equation.

...

## Unlock

This Answer NowStart your **48-hour free trial** to unlock this answer and thousands more. Enjoy eNotes ad-free and cancel anytime.

Already a member? Log in here.

The way to solve this sort of set of equations is to substitute a value for one of the variables.

If you look at the first equation, you see that you can easily get a value for y. You do that by subtracting 4x from both sides of the equation.

That gives you

y = 1-4x

So now you take that value for y and plug it in to the other equation:

4x + 3 (1-4x) = 7

4x +3 - 12x = 7

4x - 12 x = 4

-8x = 4

x = -.5

Now you can plug that value back into the first equation.

4 (-.5) + y = 1

-2 + y = 1

y = 3